Indonesia Pemanfaatan Artificial Intelligence Dalam Kewirausahaan Digital UMKM Sektor Kuliner Di Kota Potianak Pada Era Ekonomi Digital Hiperkompetitif: Studi Kaus di Kota Pontianak - Vinsensius VINSENSIUS; Ratnawati (BJRM (Bongaya Journal of Research in Management), 2026)
The rapid growth of the hypercompetitive digital economy requires Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector in Pontianak City, to adapt through the utilization of digital technologies. However, the adoption of advanced technologies, especially Artificial Intelligence (AI), remains relatively low, which may hinder business competitiveness and sustainability. This study aims to analyze the effect of Artificial Intelligence utilization and digital marketing strategies on MSME sustainability, with digital transformation capability as a mediating variable. The research adopts a quantitative approach using SPSS. Data were collected through structured questionnaires from 124 culinary MSME owners in Pontianak City selected using purposive sampling. The results are expected to indicate that AI utilization and digital marketing strategies have a positive effect on digital transformation capability and MSME sustainability. Furthermore, digital transformation capability strengthens the relationship between technology utilization and business sustainability. This study is expected to contribute to the development of digital entrepreneurship and provide insights for formulating effective MSME digital transformation strategies.